Obsessive compulsive disorder in a dog (Gaceta de Ciencias Veterinarias, 2017)
Obsessive compulsive disorder is a repetitive and affective behavior, this pathology of behavior is consistent with states of anxiety by a conflict of the animal against or toward its environment. The goal of treatment is to replace anxious responses with acceptable behavior and to prevent patient injuries from the behavior. A 2-year-old male, 10-kg-weight Beagle dog named Tito, who had injured his tail because he had been repeatedly licking it, also he was walking around himself when he got excited for some reason. Due to the context and after discard other pathologies, he was diagnosed as Obsessive Compulsive Disorder consequent to anxiety. A pharmacological treatment based on the administration of Clomipramine 1mg / kg twice a day for four months and Alprazolam 0,1 mg / kg once daily for four weeks in addition to environmental enrichment, changes in social and technical interaction Behavioral modification. After six weeks the dog had not repeated compulsive behaviors and was phased out pharmacological treatment.
Keywords: TOC; dog; pharmacotherapy; behavioral modification; environmental enrichment